Learning on the job: Rethinks and realizations about the use of eye tracking in music-reading studies - Marjaana Puurtinen (The European Association for Research on Learning and Instruction, 2022)
The application of new methods and measures in domains with few methodological traditions of that kind often presents researchers with a challenge; they may have to take up the task of developing their understanding of the phenomenon while, at the same time, creating the practices for its study. For us, the method was eye tracking, and the topic, music reading. One key characteristic of music reading is that themusic reader’s gaze moves slightly ahead of the current point of performance. This gap allows the performer to prepare for the upcoming motoric responses. In this paper, we present our 10-year-long path, describing the steps we have taken while studying this “looking ahead” in music reading. We will point out how we have, after both advances as well as setbacks, come to change our views on how best to explain the various components affecting this specific act and how it is best measured. Finally, we discuss some of the lessons we have learned, hoping in this way to provide practical suggestions for others who plan to take up methods from other domains and use them in novel ones.